Death and burial in medieval England 1066-1550 - Daniell, Christopher (London : Routledge, 1997)
Christopher Daniell establishes the role that death played in the Middle Ages. It was a theme in medieval public life, finding expression both in literature and art. Daniell explains the procedures that were involved when a person died, and discusses the literary and artistic themes associated with death. He includes the very latest research, both his own and others working in the area, including assessing archaeological discoveries. The final chapter presents a uniquely detailed survey of death from the Norman Conquest to the Reformation in the 1550s.
Includes bibliographical references (p. 209-229) and indexes.
Keywords: Death -- History; Funeral rites and ceremonies, Medieval -- England; Human remains (Archaeology) -- England; England -- Antiquities; England -- Social life and customs -- 1066-1485.